2019
DOI: 10.3390/ijerph16142465
|View full text |Cite
|
Sign up to set email alerts
|

Intervention and Public Policy Pathways to Achieve Health Care Equity

Abstract: Health care equity reflects an equal opportunity to utilize public health and health care resources in order to maximize one’s health potential. Achieving health care equity necessitates the consideration of both quantity and quality of care, as well as vertical (greater health care use by those with greater needs) and horizontal (equal health care use by those with equal needs) equity. In this paper, we summarize the approaches introduced by authors contributing to this Special Issue and how their work is cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The purpose of an effective health system is not only to improve the health of the population [1], but also to achieve equality in health [2,3]. Each public policy (not only health policy) should be focused on the fulfillment of health potential of population without disadvantages and obstacles [4]. Marmot [5] concluded that the health status of the population is an important aspect of economic life and countries can be judged on the basis of health outcomes and a fair distribution of health care across the social spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of an effective health system is not only to improve the health of the population [1], but also to achieve equality in health [2,3]. Each public policy (not only health policy) should be focused on the fulfillment of health potential of population without disadvantages and obstacles [4]. Marmot [5] concluded that the health status of the population is an important aspect of economic life and countries can be judged on the basis of health outcomes and a fair distribution of health care across the social spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Panel Unit Root Test 3) report the Driscoll-Kraay standard errors, which are used to solve the three major problems of heteroskedasticity, autocorrelation, and cross-section correlation, Columns (4) to (6) report the cluster-robust standard errors, which are used to solve the two major problems of heteroskedasticity and autocorrelation. The R 2 reported in Columns (1) to (4), (5), and (6) are Within R 2 , Overall R 2 , and Adj.R 2 , respectively. a P < 0.01, b P < 0.05, c P < 0.10.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing healthcare costs, rationalizing the use of healthcare resources, and improving access to and fairness of healthcare services are major challenges in healthcare reform efforts in many countries [ 1 , 2 , 3 , 4 , 5 ]. In China, the demand for healthcare services is vast, and the distribution of healthcare resources is inequitable [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%